"Sangeeta ratnakaram" of "Nissanka" Sarngadeva - Rangaramanuja Iyengar, R. (Wilco, 1978)
A critical survey of Karnatic music, based on Saṅgītaratnākara, a verse treatise on Indic music and dance, by Śārṅgadeva, 13th cent.